Formation of ionospheric irregularities over Southeast Asia during the 2015 St. Patrick's Day storm. Issue 12 (29th December 2016) - Spogli, Luca; Cesaroni, Claudio; Di Mauro, Domenico; Pezzopane, Michael; Alfonsi, Lucilla; Musicò, Elvira; Povero, Gabriella; Pini, Marco; Dovis, Fabio; Romero, Rodrigo; Linty, Nicola; Abadi, Prayitno; et al.
Abstract: We investigate the geospace response to the 2015 St. Patrick's Day storm leveraging on instruments spread over Southeast Asia (SEA), covering a wide longitudinal sector of the low‐latitude ionosphere. A regional characterization of the storm is provided, identifying the peculiarities of ionospheric irregularity formation. The novelties of this work are the characterization in a broad longitudinal range and the methodology relying on the integration of data acquired by Global Navigation Satellite System (GNSS) receivers, magnetometers, ionosondes, and Swarm satellites. This work is a legacy of the project EquatoRial Ionosphere Characterization in Asia (ERICA). ERICA aimed to capture the features of both crests of the equatorial ionospheric anomaly (EIA) and trough (EIT) by means of a dedicated measurement campaign. The campaign lasted from March to October 2015 and was able to observe the ionospheric variability causing effects on radio systems, GNSS in particular. The multiinstrumental and multiparametric observations of the region enabled an in‐depth investigation of the response to the largest geomagnetic storm of the current solar cycle in a region scarcely reported in literature. Our work discusses the comparison between northern and southern crests of the EIA in the SEA region. The observations recorded positive and negative ionospheric storms, spread F conditions, scintillation enhancement and inhibition, and total electron content variability. The ancillary information on the local magnetic field highlights the variety of ionospheric perturbations during the different storm phases. The combined use of ionospheric bottomside, topside, and integrated information points out how the storm affects the F layer altitude and the consequent enhancement/suppression of scintillations. Key Points: Geospace characterization of Saint Patrick's Day storm over Southeast Asia with a multiinstrumental approach is provided Postsunset scintillation inhibition has been detected and compared with the morphology and dynamics of the ionospheric F layer Meridional and zonal variations between the equatorial ionospheric anomaly crests are discussed in depth